The impact of using suture ligatures as a replacement for staplers and reducing excessive thermal energy on outcomes after pulmonary segmentectomy: a prospective cohort study - Wang, Binkui; Wang, Fangqing; Chen, Gang; Ruan, Weimin; Zhu, Zhaowang; Hu, Weijian; Zang, Lin (Frontiers in Oncology, 2025)
BackgroundThis study aims to evaluate the impact of using suture ligatures and avoiding thermal injury (hereinafter referred to as the modified measures) on clinical outcomes after pulmonary segmentectomy.MethodsA prospective randomized controlled study was conducted, involving 100 patients who met the inclusion criteria and were scheduled for single-port video-assisted thoracoscopic lung segmentectomy at our hospital from May 1, 2024, to May 31, 2025. The patients were randomly divided into an experimental group (modified measures) and a control group (traditional lung segmentectomy), followed by undergoing single-port thoracoscopic lung segmentectomy. A questionnaire was used to evaluate the incidence of cough and the intensity of cough symptoms at 2, 4, and 8 weeks postoperatively, along with related intraoperative and postoperative indicators, to verify the effectiveness and safety of the improved intraoperative bronchial protection measures in single-port thoracoscopic lung segmentectomy.ResultsThe modified measures significantly reduced the incidence of cough and symptom intensity at 2, 4, and 8 weeks postoperative. The cough scores in the experimental group were significantly better than those in the control group, with a statistically significant difference (p < 0.05). Analysis of intraoperative and postoperative indicators showed that the improved measures did not increase the surgical time and that the total intraoperative blood loss and the total drainage volume on postoperative day 3 were similar between the two groups, with no statistically significant difference (p > 0.05).ConclusionUsing suture ligatures as a replacement for staplers and minimizing thermal injury to the hilar structures based on standardized perioperative management may positively impact postoperative clinical outcomes, particularly the severity and duration of postoperative cough, leading to a significant improvement in patients’ quality of life.